Knowledge and Awareness of Community People on Dengue Fever Infection: A Cross-Sectional Study - Erum Akhter, Bilal Jawed, Azfar Athar Ishaqui, Zeeshan Ahmed, Salman Ahmed, Bilal Mustafa, Imran Ali, Moeen Ahmed, Muhammad Imran, Sadia Ghousia Baig, Afshan Siddiq, Shayan Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Pakistan has been suffering from epidemics of dengue infection in last two decades. One of the reasons of yearly high number of cases is due to lack of awareness and knowledge about prevention of dengue infection. The current study aimed to assess the level of knowledge and awareness of dengue infection common population of Karachi. Material and Methods: A cross-sectional survey-based study was carried out over a period of three months. First section comprised of demographic characteristics of participants, section two comprised of 7- items about the knowledge of dengue infection, while section three comprised of 5- items related to awareness and perception of dengue infection among participants. Results: A total of 201 participants were enrolled in the study with mean age of 26.9 years. Female participants were more as compared to male participants. Most of the participants belonged to low- or middle-income socio-economic status and had no history of dengue infection in the past. Less than half (39.8%) participants responded correctly that dengue mosquito breed in stagnant clean water. Around three-fourth population think that the chances of bite of mosquito is more in night time or dusk as compared to correct option of dawn. Around 37.3% participants were unaware that there is no vaccine available for the prevention or treatment of dengue infection. Around 30% respondents responded that antibiotics can be used for the treatment of dengue infection. Conclusion: The level of knowledge in the current study was observed to low as compared to the previous studies. The level of awareness and knowledge among common population needs to be improved among common population Keywords: Dengue, Knowledge, Awareness, Mosquito, Perception